Experimental huts trial of the efficacy of pyrethroids/piperonyl butoxide (PBO) net treatments for controlling multi-resistant populations of Anopheles funestus s.s. in Kpomè, Southern Benin - Akoton, R.; Tchigossou, G.; Djegbe, I.; Yessoufou, A.; Atoyebi, S.M.; Tossou, E.; Zeukeng, F.; Boko, P.; Irving, H.; Adeoti, R.; Riveron, J.; Wondji, C.S.; et al. (F1000 Research Ltd, 2018)
Background: Insecticides resistance in Anopheles mosquitoes limits Long-Lasting Insecticidal Nets (LLIN) used for malaria control in Africa, especially Benin. This study aimed to evaluate the bio-efficacy of current LLINs in an area where An. funestus s.l. and An. gambiae have developed multi-resistance to insecticides, and to assess in experimental huts the performance of a mixed combination of pyrethroids and piperonyl butoxide (PBO) treated nets on these resistant mosquitoes. Methods: The study was conducted at Kpomè, Southern Benin. The bio-efficacy of LLINs against An. funestus and An. gambiae was assessed using the World Health Organization (WHO) cone and tunnel tests. A released/recapture experiment following WHO procedures was conducted to compare the efficacy of conventional LLINs treated with pyrethroids only and LLINs with combinations of pyrethroids and PBO. Prior to huts trials, we confirmed the level of insecticide and PBO residues in tested nets using high performance liquid chromatography (HPLC). Results: Conventional LLINs (Type 2 and Type 4) have the lowest effect against local multi-resistant An. funestus s.s. and An. coluzzii populations from Kpomè. Conversely, when LLINs containing mixtures of pyrethroids and PBO (Type 1 and Type 3) were introduced in trial huts, we recorded a greater effect against the two mosquito populations (P < 0.0001). Tunnel test with An. funestus s.s. revealed mortalities of over 80% with this new generation of LLINs (Type 1 and Type 3),while conventional LLINs produced 65.53 ± 8.33% mortalities for Type 2 and 71.25 ±7.92% mortalities for Type 4. Similarly, mortalities ranging from 77 to 87% were recorded with the local populations of An. coluzzii. Conclusion: This study suggests the reduced efficacy of conventional LLINs (Pyrethroids alone) currently distributed in Benin communities where Anopheles populations have developed multi-insecticide resistance. The new generation nets (pyrethroids+PBO) proved to be more effective on multi-resistant populations of mosquitoes.